Analysis of Mastitis Cases on Modern Dairy Farms in Blitar Regency, Indonesia - Zalizar Lili; Hendraningsih Listiari; Hidayati Asmah; Sutawi Sutawi; Wijayanto Wijayanto; Mariyam Dewi; Rahmaita Utarid Irma; Dharmawan Rachmad; Yaro Abubakar (E3S Web of Conferences, 2023)
This study aims to determine: i) the relationship between lactation level and clinical mastitis, ii) bacteria that cause clinical mastitis and iii) the incidence rate of the disease based on Days in Milk (DIM). The research location was carried out at a modern dairy farm in Blitar Regency, Indonesia. Clinical mastitis dairy divided into nine lactation periods including: lactation period (LP) 1 (168 heads); LP 2 (224 heads); LP 3 (153 heads); LP 4 (102 heads); LP 5 (51 heads); LP 6 (14 heads); LP 7 (7 heads); LP 8 (1 head); LP 9 (3 heads). Data were analyzed using simple regression and descriptive analysis. There was a linear increase in the percentage of mastitis incidence at the lactation period in modern dairy farm, y = 1.9483x + 14.938 following R² = 0.2315. The worst incidence occurred during the sixth lactation (43.75 %). Streptococcus uberis was identified as the most common bacteria causing mastitis (55.19 %). The highest incidence of mastitis occurred in Days in Milk (DIM) > 150 d (48.55 %), followed by DIM < 75 d (21.44 %). Furthermore, the second lactation with DIM > 150 d (15.63 %) had the greatest mastitis incidence.